The Effect of Abortion Policies on Fertility and Human Capital in Sub-Saharan Africa - Arcangelo Dimico (Global Labor Organization (GLO), 2025)
I evaluate the impact of abortion policies in sub-Saharan Africa to understand the potential consequences of a reduced international support for women's rights following the overturn of Roe v. Wade. I find that decriminalizing abortion reduces fertility through two complementary channels. For households at the top of the wealth distribution, the effect manifests as a reduction in excess fertility, which is more pronounced among lower-educated women due to their lower likelihood of using contraception. For households at the bottom of the wealth distribution, the impact runs through a decline in the number of children with a low survival probability. This latter effect is more pronounced among highly educated women, who are more likely to control their own health-related decisions and view abortion as a viable option. I also find that while women's education levels rise after decriminalization, this does not lead to better labor market opportunities. Children born afterwards tend to achieve higher levels of education.
Keywords: O15; L1; J13; J16; K38; 330; Abortion; fertility; child mortality; human capital